2018
DOI: 10.1016/j.wjorl.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in differential sensitivity and temporal resolution in morning‐type and evening‐type individuals with normal hearing

Abstract: The present study attempts to determine diurnal changes by testing the differential sensitivity and temporal resolution in morning-type, evening-type, and intermediate-type individuals with normal hearing. Thirty participants with normal hearing were divided into morning-type, evening-type, and intermediate-type using “Morningness–Eveningness Questionnaire”. The tests of differential sensitivity and temporal resolution were administered to all the participants in the morning and evening, respectively. The diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Surprisingly, our results revealed no statistically significant effect of morning or evening that influenced the tasks administered except one task in which the midpoint scores of forward span showed statistically significant better scores exhibited by morning-type individuals when tested during the morning. This is in agreement with the findings reported in studies on auditory temporal processing, which had shown significant diurnal effects (Nikhil et al, 2018;Prakash et al, 2021). Their studies revealed a better auditory temporal processing abilities during the morning for morning-type individuals, and similar improvements in scores were noted for evening-type individuals when tested during the evening.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Surprisingly, our results revealed no statistically significant effect of morning or evening that influenced the tasks administered except one task in which the midpoint scores of forward span showed statistically significant better scores exhibited by morning-type individuals when tested during the morning. This is in agreement with the findings reported in studies on auditory temporal processing, which had shown significant diurnal effects (Nikhil et al, 2018;Prakash et al, 2021). Their studies revealed a better auditory temporal processing abilities during the morning for morning-type individuals, and similar improvements in scores were noted for evening-type individuals when tested during the evening.…”
Section: Discussionsupporting
confidence: 91%
“…Second, as mentioned by Kerkhof (1982), where the P450 amplitude showed no significant diurnal change due to the fluctuation in the processing of the different aspects of tasks performed, in our case, the auditory working memory may show different processing at the cortical level which does not involve any diurnal effects. Third, unlike other temporal resolution tasks which were performed in studies by Nikhil et al (2018) and Prakash et al (2021), during an ongoing trial in which digits are presented, the subvocal rehearsal performed by the subjects activates various regions of the frontal lobe and other associated structure which could possibly strengthen the maintenance of stimuli in mind and overcome the inhibitory controls linked with the time of the day (Kumar et al, 2016). Fourth, there could be an interplay of long-term memory and visual memory when using stimuli like digits which has got a defined semantic and graphical representation in an individual's inventory compared to tonal signals, which would enhance the encoding and maintenance of digits stimuli in the sensory memory (Visscher et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronotype as an indicator of circadian rhythms represents a continuous spectrum ranging from eveningness to morningness [ 14 , 15 ]. Evening-type individuals are more active and perform better in the evening than in the morning and circadian processes (such as cortisol and body temperature) peaks in the evening, while it is vice versa for morning-type individuals [ 16 ]. More importantly, evening-type individuals are more likely to suffer from the desynchrony between circadian rhythms and environmental demands [ 14 ].…”
Section: Introductionmentioning
confidence: 99%